Hrozný and Hittite
1 online resource.
Keywords: This volume collects 33 papers that were presented at the international conference held at the Faculty of Arts, Charles University in November 2015 to celebrate the centenary of Bedřich Hrozný’s identification of Hittite as an Indo-European language. Contributions are grouped into three sections, “Hrozný and His Discoveries,” “Hittite and Indo-European,” and “The Hittites and Their Neighbors,” and span the full range of Hittite studies and related disciplines, from Anatolian and Indo-European linguistics and cuneiform philology to Ancient Near Eastern archaeology, history, and religion. The authors hail from 15 countries and include leading figures as well as emerging scholars in the fields of Hittitology, Indo-European, and Ancient Near Eastern studies.